Transition towards a sustainable biobased economy - Morone, Piergiuseppe; Clark, James H. (Royal society of chemistry, 2020)
This book promotes the development of sustainability for the assessment of biobased products, which are fundamental to the establishment of a cutting-edge sustainable bioeconomy.
Keywords: Environmental economics.; Biotechnology.; Sustainable development -- Economic aspects.; Bioengineering.; elektronické knihy; electronic books